Diagnosis and Treatment of Peptic Ulcer in Adults (Clinical Guidelines of the Russian Gastroenterological Association, Russian Society of Colorectal Surgeons and the Russian Endoscopic Society) - V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2020)
Aim. These clinical recommendations present up-to-date methods for the diagnosis and treatment of peptic ulcer. The recommendations are intended for gastroenterologists and general practitioners.General provisions. Peptic ulcer (PU) represents a chronic relapsing disease occurring with alternating periods of exacerbation and remission. The main manifestation of the disease is the formation of a defect (ulcer) in the wall of the stomach and duodenum. Most cases of peptic ulcer are pathogenetically associated with the infection of H. pylori. PU can be an independent disease or represent symptomatic ulcers of the stomach and duodenum (medicinal, as a result of stress or endocrine pathologies, associated with chronic diseases of internal organs). In the absence of contraindications, esophagogastroduodenoscopy is recommended for all patients with suspected ulcer with the purpose of confirming the diagnosis. In order to determine indications for eradication therapy, all ulcer patients should be tested for the presence of H. pylori using a 13C-breath test or a stool antigen test. In the case of simultaneous endoscopy, rapid urease test can be used. For the prevention of subsequent relapses of ulcer, all PU patients with confirmed H. pylori should undergo eradication therapy. In addition, in order to achieve ulcer healing, 4–6 week antisecretory therapy with proton pump inhibitors is recommended. Clinical recommendations contain criteria for assessing the quality of medical care, an algorithm of the doctor’s actions, as well as information for patients.Conclusions. These clinical recommendations present modern ideas about the etiology and pathogenesis of peptic ulcer disease, its clinical manifestations, methods of laboratory and instrumental diagnostics and basic approaches to conservative and surgical treatment.